Effects of nutrition counselling on iron deficiency anemia in pregnancy - Mangkalard, Preeyapat; Ruekngarm, Lawan; Ponta, Supawadee (Life Sciences, Medicine and Biomedicine, 2022)
Anemia is a significant public health concern in pregnant women and women of reproductive age globally. The prevalence of anemia in Thailand was approximately 36.7%. Common causes of anemia were iron deficiency anemia (IDA) and beta-thalassemia trait (BTT). World Health Organization (WHO) recommends that dietary adjustments focusing on iron-rich foods foster the improvement of IDA and IDA with BTT. This study aimed to evaluate the effect of nutrition counselling in pregnant women with IDA on anemia parameters and dietary intake records. Retrospective data were obtained from the Division of Nutrition and Antenatal Care (ANC) Clinic at Bamrasnaradura Infectious Diseases Institute (BIDI) in Nonthaburi, Thailand. Nutrition Care Process Model was used in nutrition service at BIDI. During the second trimester, nutrition counselling was provided at the ANC Clinic by a dietitian routinely based on WHO guidelines for nutritional anemia. The anemia parameters and dietary intake records were recorded during ANC visits at the second and third trimesters. A paired t-test was used to evaluate differences within each group. Collected data from 61 pregnant women with anemia were analyzed (IDA: 55; BTT: 6). In the third trimester, the changes in hematocrit levels were significantly high in both IDA (p ≤ 0.001) and BTT groups (p = 0.016). In addition, the improvement in daily energy consumption and iron-rich foods was significantly observed in both groups (p ≤ 0.001). In conclusion, the delivery of nutrition counselling focusing on iron-rich foods significantly enhanced IDA parameters and eating behaviours, including increased hematocrit levels, and improved daily energy intake and iron-rich foods intake among pregnant women with anemia.